Strategi Pengembangan Pariwisata Kota Batu Dalam Perspektif Entrepreneurial Government (Studi pada Dinas Pariwisata dan Kebudayaan Kota Batu) - Alfi Alhuda (Jurnal Administrasi Publik, 2015)
Abstract: Batu City Tourism Development Strategy in Entrepreneurial Government Perspective (Study In the Department of Tourism and Culture in Batu City). Batu City is one city in Indonesia which are focus on develop a tourism sector and yield positive results of tourism development. Datas of reception GDP Batu City showing the tourism is a growth sector and evolve into leading sectors which gives of all sector in economic growth of Batu City. Seeing of this phenomenon, so strategy of tourism development in Batu City here interest to be research with entrepreneurial government perspective. Entrepreneurial government is a idea to transform the spirit of entrepreneur into public sector, so government must to act innovative, creative, capable to make decisions about investments, and capable to identify there opportunities. The method in this research is qualitative description. The results of the research showing, are points in accordance than tourism development strategy in Batu City with entrepreneurial government approaches, such as services of licensing, investment, partnerships, and community empowerment program. Keywords: Strategy of development tourism, entrepreneurial government Abstrak: Strategi Pengembangan Pariwisata Kota Batu dalam Perspektif Entrepreneurial Government (Studi pada Dinas Pariwisata dan Kebudayaan Kota Batu). Kota Batu merupakan salah satu kota di Indonesia yang sedang fokus dalam mengembangkan sektor pariwisata dan menunjukkan perkembangan positif dari pengembangan pariwisata. Berdasarkan data penerimaan PDRB Kota Batu, sektor pariwisata bergerak menjadi sektor unggulan yang dominan dalam menopang pertumbuhan ekonomi di Kota Batu. Melihat fenomena ini, maka strategi dari pengembangan pariwisata di Kota Batu menarik untuk diteliti dengan menggunakan perspektif entrepreneurial government. Entrepreneurial government merupakan gagasan yang berkembang untuk mentransformasikan semangat kewirausahaan pada sektor publik, yakni pemerintahan yang mampu untuk bersikap inovatif, kreatif, mampu membuat keputusan tentang investasi, dan kemampuan untuk mengidentifikasi berbagai peluang yang ada. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan, terdapat poin-poin dalam strategi pengembangan pariwisata Kota Batu yang bersinggungan dengan pendekatan-pendekatan entrepreneurial government, diantaranya dalam bidang pelayanan perijinan, investasi, kemitraan, dan program pemberdayaan masyarakat. Kata Kunci: Strategi pengembangan pariwisata, entrepreneurial government